ANALISIS TOKOH DAN TINDAKAN OTORITER DALAM CERPEN RIPIN KARYA UGORAN PRASAD - Noor Komari Pratiwi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This article aims to analyze the figure and authoritarian attitudes in Ugoran Prasad's short story. This short story illustrates the dimensions of social life, the relationship between one character and other figures, both in the family environment and the community in the era of the New Order government. The method used is descriptive qualitative method and literature study. Ripin's short story reveals the life of Ripin as a victim of an authoritarian family head. After analyzing the Ripin short story, it can be concluded that there is a true picture of authoritarian actions taken by the head of the family towards his wife and children. In addition, a picture of the New Order government's authoritarian actions towards the community in the 1980s was also obtained. Although Ripin's short stories describe violence caused by the authoritarian actions of the head of the family towards children and wife, as well as violence due to the authoritarian actions of the New Order government, but many values ​​can be taken as wisdom.